Perfil epidemiológico de las personas privadas de libertad del establecimiento penitenciario penal de cambio puente. período 2010 - 2011 - Betancourt Sarmiento, Johana del Pilar (2014)
This research is a descriptiva cross, with an ecological approach - Epidemiological, which had as its overall objective Meet the Epidemiological Profile of Persons Deprived of Liberty Penitentiary Penal Rate Bridge. Period 20i0-20ii. The population will consist of i00% (20i O Ni = 792, 20ii N2 = i 076) of the detainees of Criminal Penitentiary Rate Bridge. For data collection will use a tab on the epidemiological profile of the detainees. Processing and statistical analysis was performed on specialized software Statistics and Epidemiology (EPIINFO); getting itself to the following conclusions: • There are high levels of overcrowding in detainees for 20ii (95.2%) compared to 20i0 with less overcrowding (38.4%). • Socio-demographic characteristics of persons deprived of liberty that prevailed are male with an average of 30-39 years of age; leve! of secondary education. • The legal status of the detainees that predominates is sentenced. • The type of offense for persons deprived of liberty is the most prevalent crime against the continuad heritage crime against public safety and crime against freedom. • In 20i O and 20ii the prevailing admitted for the first time (55.4% and 57.4% respectively), followed by the smaller proportion who were readmitted 2 times (20i O and 20ii 2i.0% 23.2%). • The most prevalent for years 20i O and 20ii diseases are diseases of the respiratory system and infectious diseases. • The prevalence of pulmonary tuberculosis in detainees is relatively higher in 20ii (2i.4/i 000 persons deprived of freedom) compared to 20i O (i7.7/i000 persons deprived of liberty). • The most common type of tuberculosis of the detainees is pulmonary for the years 20i0 and 20ii. • The detainees, received in 20i0 the scheme i (85.7%) and Scheme ii (i4.3%) and in 20ii received one treatment of Scheme i (i00%). • In the syndromic management of STis is the most prevalent vaginal discharge, with the highest incidence in 20i O compared to 20ii. In the aetiological STI management is the most prevalent genital herpes (20i O 56.8% 20ii 58.i ), followed by syphilis (20i0 24.3% 20ii 32.2%). • An prevalence in 20i O of 7.6/i000 persons and in 20ii a prevalence of 6.5/i000 person is observed.